In Praise of Lunatics - Franco Cambi (Firenze University Press, 2011)
The author begins his reflection on the evocative function of the moon (from a cultural, poetic, social and popular point of view) suffering since 1969, when man landed on the moon. The moon has always held a high and consistent role as a symbol and as such has accompanied the history of human culture. It has been said that the moon was the star after the sun has most excited the admiration of man from its very beginning and it has led him to the adoration. On a more spiritual confidant, the moon is the secret of moods and impregnates itself poetry, especially that lyric. The author reflects, then, on at least three ways to "become" moody.